Surface modification of polypropylene for enhanced layer‐by‐layer deposition of polyelectrolytes. Issue 7 (10th April 2018) - Hachim, Daniel; Brown, Bryan N.
Abstract: We have performed three distinct plasma enhanced chemical vapor deposition procedures that can be widely and consistently used in commercially available plasma systems to modify the surface of hydrocarbon‐based biomaterials such as polypropylene. In particular, we have evaluated the feasibility of these procedures to provide consistent and stable charged substrates to perform layer‐by‐layer (LbL) coatings. Surface characterization of both plasma and LbL coatings were done using X‐ray photoelectron spectroscopy, attenuated total reflection—Fourier transform infrared spectroscopy, contact angle measurements and surface staining. Results showed successful surface grafting of functional groups in all plasma procedures that led to increased hydrophilicity and uniform LbL coatings with different efficiencies. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2078–2085, 2018